Identities and their aspects in the novel Khuzama by Sinan Antoon - IBTISAM ALI MAHMOOD, Researcher; Azad Abdul Rashid, Assistant Professor Dr. (lark, 2026)
This research analyzes the problem of identity and it is multiple manifestations in Sinan Antoon novel (Khuzama) through a critical approach based on the concept of identity and crises in the social and cultural contexts the study focused on five main axes the self and the other as the novel reveals the struggle of the self with the image of the other and representations in the collective consciousness religious identity ehich is manifested in the dialectic of belonging and national identity which appears through connection to the homeland language and shared history social identity which is fromed through relationships and roles within society and the disintegration or cohesion that occurs due to events and cultural identity which emerges through the conflict between heritage and openness to other cultures from here the novel came to present a rich narrative space that reflects the ruptures of identity in contemporary lagi reality.
Keywords: Identities - Crises - Khuzama novel